Exchange rate pass-through into German import prices: A disaggregated perspective - Joscha Beckmann; Ansgar Belke; Florian Verheyen (Research On Money in the Economy (ROME), 2013)
This study analyzes the exchange rate pass-through into German import prices based on disaggregated data taken on a monthly basis between 1995 and 2012. Our main contribution is twofold: firstly, we employ various time-series techniques to analyze data for different product categories, and also cointegration techniques to carefully distinguish between shortrun and long-run pass-through coefficients. Secondly, in a panel data approach we estimate time-varying pass-through coefficients and explain their development with regard to various macroeconomic factors. Our results show that long-run pass-through is only partly observable and incomplete, while short-run pass-through shows a more unique character, although heterogeneity across product groups does exist. We are also able to identify several macroeconomic factors which determine changes in the degree of pass-through, which is especially relevant for policymakers.
Keywords: E31; F10; F14; 330; exchange rate pass-through; Germany; cointegration; time-varying coefficient model